Perception of parents about second hand smoke on the health of their children: an ethnographic study - Fabiane Alves de Carvalho Ribeiro; Micaele Kedma Ribeiro de Moraes; Joyce Cristina de Morais Caixeta; Jullieth Nadja da Silva; Amanda Sanches Lima; Samara Lamounier Santana Parreira; Viviane Lemos Silva Fernandes (Sociedade de Pediatria de São Paulo, 2015)
Objective: To analyze the perception of parents about secondhand smoking in their children's health. Methods: Ethnographic qualitative and quantitative study. We sought the point of view and understanding of the parents who were active smokers in relation to environmental tobacco smoke (ETS) and secondhand smoking. Mothers and fathers who are active smokers and that live with their children from seven different public schools in the city of Anápolis, Midwest Brazil, were interviewed in the first semester of in a reserved room in the schools. A descriptive and qualitative analysis was carried out through the ethnography. Results: 58 parents with an average time of smoking of 15.3 years and an average quantity of cigarettes smoked per day of 2 were interviewed. Among them, 59% did not know what ETS was, and 60% stated knowing what a secondhand smoker was. However, when questioned about their children as secondhand smokers, 52% did not consider them to be. Some parents knew some of the effects of secondhand smoking in the health of their children. However, the majority (52%) of them did not believe that their children would suffer any respiratory impairment or did not know about these impairments. Conclusions: Children were exposed to environmental tobacco pollution in their residence if one considers parental duration of smoking and average of cigarettes smoked per day. There was a lack of knowledge of the parents about ETS, secondhand smoking and the evils that cigarettes could cause in the health of their children.